Triggered, Nanostructured Biodegradables (TNBs) for Surgical Implants - Gordon, Richard; M. Levin, Stephen; C. Gebeshuber, Ille (Micro and Nanosystems, 2011)
In medicine, objects that need to be removed later - such as stents - are commonly placed in patients, with the time of removal dependent on progress of the patient. In these cases biodegradable materials that last for a specific time may not be suitable. We propose a new class of nanostructured materials that can hold their form as long as wanted, Triggered, Nanostructured Biodegradables (TNBs), that can be disintegrated to micro- or nanoscaled components when externally triggered on command to do so. DNA nanotensegrity microstructures, metastable foams, nanobots and other bioinspired disintegratable scaffold structures are given as potential examples.
Keywords: tensegrity